Comparison of the inhibitory properties of the fruit component naringenin and its glycosides against OATP1A2 genetic variants. (October 2022) - Araki, Naoya; Morita, Tokio; Akiyoshi, Takeshi; Kataoka, Hiroki; Yajima, Kodai; Katayama, Kazuhiro; Imaoka, Ayuko; Ohtani, Hisakazu
Abstract: Non-synonymous genetic variants of organic anion-transporting polypeptide (OATP) 1A2 with altered transport activity have been identified. Naringin and narirutin, which are found in grapefruit, and their aglycon naringenin inhibit OATP1A2. However, their inhibitory effects on OATP1A2 variants have not been investigated, nor has the influence of their molecular structure, such as the number of sugar moieties, on their inhibitory potency. This study aimed to investigate the inhibitory effects of naringenin, its monosaccharide glycoside prunin, and its disaccharide glycosides naringin and narirutin on fexofenadine (FEX) uptake by OATP1A2 variants (Ile13Thr, Asn128Tyr, Ala187Thr, and Thr668Ser). Naringin, narirutin, and prunin inhibited FEX (0.3 μM) uptake by all of the examined OATP1A2 variants in a concentration-dependent manner. Compared with those for the wild type, the inhibition constants ( K i ) of naringin, narirutin, and prunin for the Ala187Thr variant were significantly increased by 3.36-fold, 7.55-fold, and 10.6-fold, respectively. Naringenin inhibited all of the OATP1A2 variants, except Ala187Thr, concentration-dependently. The order of inhibitory potency was as follows for all variants: aglycone > monosaccharide glycoside > disaccharide glycosides. These results suggest that the Ala187Thr variant is less vulnerable to inhibition by naringenin and its glycosides. Moreover, greater glycosylation of naringenin reduces its inhibitory potency against OATP1A2.